Differential effects of high-temperature stress on nuclear topology and transcription of repetitive noncoding and coding rye sequences - Tomás, D. (2013)
The plant stress response has been extensively characterized at the biochemical and physiological levels. However, knowledge concerning repetitive sequence genome fraction modulation during extreme temperature conditions is scarce. We studied high-temperature effects on subtelomeric repetitive sequences (pSc200) and 45S rDNA in rye seedlings submitted to 40 ° C during 4 h. Chromatin organization patterns were evaluated through fluorescent in situ hybridization and transcription levels were assessed using quantitative real-time PCR. Additionally, the nucleolar dynamics were evaluated through fibrillarin immunodetection in interphase nuclei. The results obtained clearly demonstrated that the pSc200 sequence organization is not affected by high-temperature stress (HTS) and proved for the first time that this noncoding subtelomeric sequence is stably transcribed. Conversely, it was demonstrated that HTS treatment induces marked rDNA chromatin decondensation along with nucleolar enlargement and a significant increase in ribosomal gene transcription. The role of noncoding and coding repetitive rye sequences in the plant stress response that are suggested by their clearly distinct behaviors is discussed. While the hetero-chromatic conformation of pSc200 sequences seems to be involved in the stabilization of the interphase chromatin architecture under stress conditions, the dynamic modulation of nucleolar and rDNA topology and transcription suggest their role in plant stress response pathways